Lateral Wall Implant as an Adjunct to Lateral Wall Orbital Decompression in Severe Thyroid Eye Disease. Issue 2 (March 2022) - Men, Clara J.; Gur, Zvi; Ko, Audrey C.; Liu, Catherine Y.; Korn, Bobby S.; Kikkawa, Don O.
Abstract : Purpose: To describe the use of a lateral wall implant as an adjunct in lateral orbital wall decompression in severe thyroid eye disease. Methods: This study is a retrospective review of 6 patients who underwent prior orbital decompression but had persistent proptosis. These patients underwent lateral wall decompression with adjunct lateral wall implant placement with a manually vaulted 0.6-mm polyethylene-coated titanium mesh implant. Data collection included: visual acuity, intraocular pressure, exophthalmometry, ocular motility, eyelid position, and complication rates. Results: Eight orbits in 6 patients underwent maximal lateral wall decompression and reconstruction using the polyethylene-coated titanium implant. Four males and 2 females were included with ages ranging from 25 to 73 years. Visual acuity improved an average of 2.4 lines (range 0–5 lines). Intraocular pressure improved an average of 7.5 mm Hg (2–13 mm Hg). There was reduction of proptosis by 3.4 mm on average (1–7 mm). Upper eyelid retraction improved on average by 1.8 mm (0–5 mm). Horizontal eye movements improved by 11% on average (−3.1% to +25%). Excellent cosmesis was achieved with no visible temple deformity, trismus, conjunctival scarring, orbital hemorrhage, or vision loss. Conclusions: The amount of volume created in lateral wall decompression is limited by the amount of native bone present and the temporalis muscle. In severe or recalcitrant cases, the authors propose the placement of a lateral wall implant as an adjunct to laterally displace the temporalis muscle and create additional volume. This technique accomplishes further reduction of proptosis in patients who have undergone prior orbital decompression. Abstract : A manually shaped and vaulted, polyethylene barrier titanium implant creates additional orbital volume to achieve further exophthalmos reduction in severe or recalcitrant thyroid eye disease.